The matching of sinus arrhythmia to respiration: Are trauma patients without serious injury comparable to healthy laboratory subjects? - Xiaoxiao Chen; Reisner, Andrew T.; Liangyou Chen; Edla, Shwetha; Reifman, Jaques (2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2014)
We sought to better understand the physiology underlying the metrics of heart rate variability (HRV) in trauma patients without serious injury, compared to healthy laboratory controls. In trauma patients without serious injury (110 subjects, 470 2-min data segments), we studied the correlation between sinus arrhythmia (SA) rate, heart rate (HR), and respiratory rate (RR). Most segments with 2.4 <; HR/RR <; 4.8 exhibited SA-RR matching, whereas rate matching was absent in 81% of the segments with HR/RR <; 2.4 and in 86% of the segments with HR/RR > 4.8. The findings were comparable, in some cases remarkably so, to previous reports from healthy laboratory subjects. The presence (or absence) of SA-RR matching, when SA is largely controlled by respiration, can be anticipated in this trauma population. This work provides a valuable step towards the definition of patterns of HRV found in trauma patients with and without life-threatening injury.